Umiejętność obserwacji i rysowania przez dzieci brył a uzdolnienia matematyczne - Piwowarska, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Podejmowane od drugiej połowy XIX w. problemy badawcze rozwiązywane za pomocą narzędzia badawczego, jakim był rysunek, dotyczyły wielu obszarów życia, w tym edukacji plastycznej i matematycznej. Ważną kwestią postępowania badawczego stało się ustalenie zależności między zdolnościami matematycznymi dzieci a umiejętnościami odtwarzania kształtów obserwowanych przedmiotów. Postawiony problem dotyczył różnic istniejących między rysunkami brył (sześcian, ścięty stożek), wykonanych przez 8–9-letnie dzieci o różnym poziomie uzdolnień matematycznych (bez wyraźnych uzdolnień matematycznych i o takowych). Na podstawie wskazań nauczycieli odnoszących się do uzdolnień matematycznych uczniów wyodrębniono dwa zestawy prac plastycznych obrazujących obserwowane bryły, a ich analiza pozwoliła określić wstępne ustalenia przeprowadzonych badań o charakterze pilotażowym.

The research issues, which were examined since the second half of the 19th century and involved a picture as a research tool, referred to many spheres of human life, including art education as well as mathematics education. It became an important research issue to define the relation between children’s mathematical skills and their ability to present shape of observed objects. The problem concerned differences that might be observed between presentations of solid figures (cubes, truncated cone). The pictures were drawn by children at the age of 8–9 years with different levels of mathematical skills (children who had an aptitude for maths and those without mathematical aptitude). Based on teacher’s information regarding the pupils’ mathematical skills, two sets of art works were distinguished. Each of them comprised drawings that presented solid figures the children observed. Analysis of these pictures made it possible to define preliminary outline of the pilot study.
Ability to observe and draw solid figures by children and their mathematical skills
Keywords: uczeń; obserwacja; bryła; uzdolnienia; matematyka; pupil; observation; solid figure; aptitude; mathematics